Creating glycoside diversity through stereoselective carboboration of glycals - Zhenpeng Shen; Yue Yu; Dong Wu; Zhisen Wei; Weiyu Kong; Yangyang Li; Guoyin Yin (Nature Communications)
Abstract Site-specific modification of glycosides to enhance or alter the physiological properties of the parent molecule has become a highly attractive strategy in drug development. However, creating glycoside building blocks with multiple diversifiable positions from readily available sugar precursors remains a challenging task. Herein, we present a highly regio- and stereoselective nickel-catalyzed carboboration of glycals, which offers a platform for generating glycoside diversity with diverse C1 and C2 modification potential. Specially, the integration of a readily modifiable boronate group at the C2 position markedly amplifies the versatility of this approach, furnishing a universal method for swiftly generating diverse rare sugars with C2-site modifications through expedited downstream transformations. This method demonstrates a broad substrate scope and tolerates various functional groups and complex natural or drug molecular architectures. Moreover, we illustrate the synthetic potential of this method through the synthesis of a diverse array of analogs of both natural products and pharmaceuticals.